1998
DOI: 10.1126/science.281.5376.568
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Mechanism for Ligand Antagonism

Abstract: The ratio of late to early events stimulated by the mast cell receptor for immunoglobulin E (IgE) correlated with the affinity of a ligand for the receptor-bound IgE. Because excess receptors clustered by a weakly binding ligand could hoard a critical initiating kinase, they prevented the outnumbered clusters engendered by the high-affinity ligands from launching the more complete cascade. A similar mechanism could explain the antagonistic action of some peptides on the activation of T cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
150
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(158 citation statements)
references
References 40 publications
7
150
0
1
Order By: Relevance
“…Signals downstream of aggregated Fc⑀RI appear to occur as a complex network sensitive to both the presence and the amount of an activated protein or generated lipid, as well as kinetic proofreading (42,43). Signal transduction in the RBL-2H3 cell is in part regulated by the shuttling of limited amounts of the Lyn kinase that initiates a cascade of phosphorylation events (44).…”
Section: Discussionmentioning
confidence: 99%
“…Signals downstream of aggregated Fc⑀RI appear to occur as a complex network sensitive to both the presence and the amount of an activated protein or generated lipid, as well as kinetic proofreading (42,43). Signal transduction in the RBL-2H3 cell is in part regulated by the shuttling of limited amounts of the Lyn kinase that initiates a cascade of phosphorylation events (44).…”
Section: Discussionmentioning
confidence: 99%
“…[106,107] Ligand-induced sequestering of key signaling proteins also can cause antagonist-or agonist-like effects. [108,109] Thus, rather than terming multivalent ligands agonists or antagonists, we refer to them as either multivalent effectors or inhibitors. [84] Inhibitors block receptor function and multivalent effectors activate cellular processes.…”
Section: Definitions Of Multivalent Ligand Structure and Functionmentioning
confidence: 99%
“…Although much is known about the role of Fc receptors (such as the high affinity receptor for IgE, Fc RI), TLRs, and a G protein-coupled receptors (2) on mast cell activation, the influence of the microenvironment in promoting mast cell responses is just beginning to be explored (3,4). Whether a stimulus induces mast cell granule exocytosis (5) and cytokine production or selectively induces just the latter has been demonstrated to be partly dependent on the strength of the stimulus (6,7). These studies showed that the cell's response is governed by kinetic proofreading parameters (molecular events) that must occur to achieve the particular response.…”
mentioning
confidence: 99%